Pengaruh Service Performance Terhadap Nilai Sekolah, Kepuasan Dan Wom Siswa Era Pandemi (Studi Kasus Pada Smp Bruder Pontianak) - Beata Komdia Jumianti Barkah Rahmadania (Universitas Tanjungpura, 2021)
AbstractThis writing was carried out at SMP educational institutions in Pontianak City with the aim of seeing the level of satisfaction of students and parents of students during online learning during the COVID-19 pandemic so that schools can provide quality service performance. The purpose of this study was to examine and analyze the effect of service performance on school grades, satisfaction and WOM of students in the pandemic era (Case Study at SMP Bruder Pontianak). The form of this research is to use a survey. Data collection uses primary data in the form of questionnaires and interviews and secondary data in the form of data sourced from the SMP Bruder Pontianak. The sample uses a purposive sample. The sample in this study were parents of 100 students. The results of this study indicate that service performance has an effect on customer value. Second, service performance has no effect on student satisfaction. Third, customer value affect student satisfaction. Fourth, customer values affect WOM. Fifth, student satisfaction has an effect on WOM. Suggestions in this study are first to improve service performance to be even better because with better service performance it will lead to satisfaction for students and guardians of students so that later it can affect WOM where students or guardians of students can recommend SMP Bruder Pontianak as a secondary school after his son graduated from elementary school and with a good service performance it will also increase the school value of the SMP Bruder Pontianak. Second. Apart from service performance, there are still many factors that can be a factor to increase customer value, satisfaction and WOM so that periodic evaluations must always be carried out so that the SMP Bruder Pontianak can be better in the future.Keyword : Service Performance, Customer Value, Satisfaction dan Wom